Risk factors for cardio-cerebrovascular events among patients undergoing continuous ambulatory peritoneal dialysis and their association with serum magnesium - Penglei Li; Tiegang Lv; Liping Xu; Wenlu Yu; Yuanyuan Lu; Yuanyuan Li; Jian Hao (Renal Failure)
Serum magnesium levels exceeding 0.9 mmol/L are associated with increased survival rates in patients with CKD. This retrospective study aimed to identify risk factors for cardio-cerebrovascular events among patients receiving continuous ambulatory peritoneal dialysis (CAPD) and to examine their correlations with serum magnesium levels. Sociodemographic data, clinical physiological and biochemical indexes, and cardio-cerebrovascular event data were collected from 189 patients undergoing CAPD. Risk factors associated with cardio-cerebrovascular events were identified by univariate binary logistic regression analysis. Correlations between the risk factors and serum magnesium levels were determined by correlation analysis. Univariate regression analysis identified age, C-reactive protein (CRP), red cell volume distribution width standard deviation, red cell volume distribution width corpuscular volume, serum albumin, serum potassium, serum sodium, serum chlorine, serum magnesium, and serum uric acid as risk factors for cardio-cerebrovascular events. Among them, serum magnesium ≤0.8 mmol/L had the highest odds ratio (3.996). Multivariate regression analysis revealed that serum magnesium was an independent risk factor, while serum UA (<440 μmol/L) was an independent protective factor for cardio-cerebrovascular events. The incidence of cardio-cerebrovascular events differed significantly among patients with different grades of serum magnesium (χ2 = 12.023, p = 0.002), with the highest incidence observed in patients with a serum magnesium concentration <0.8 mmol/L. High serum magnesium levels were correlated with high levels of serum albumin (r = 0.399, p < 0.001), serum potassium (r = 0.423, p < 0.001), and serum uric acid (r = 0.411, p < 0.001), and low levels of CRP (r = −0.279, p < 0.001). In conclusion, low serum magnesium may predict cardio-cerebrovascular events in patients receiving CAPD.